Controllable fabrication of immobilized ternary CdS/Pt–TiO2 heteronanostructures toward high-performance visible-light driven photocatalysis1. Issue 27 (21st July 2015) - Gao, Huazhen; Wang, Honge; Jin, Youlai; Lv, Jun; Xu, Guangqing; Wang, Dongmei; Zhang, Xinyi; Chen, Zhong; Zheng, Zhixiang; Wu, Yucheng
<x xml:space="preserve">Abstract</x> Immobilized TiO2 nanotube arrays (NTAs) co-modified with Pt and CdS nanoparticles were fabricated by using the combination of photoreduction and chemical bath deposition methods.